An uncommon side effect of linezolid: Black hairy tongue. Issue 4 (27th December 2021) - Sivaraman, Shanmugapriyan; Gomathi Radhakrishnan, Gokul; Manogaran, Rajesh; Cheriyan, Binoy Varghese
Abstract: Linezolid therapy is known to cause black hairy tongue, which is benign and reversible. A 65‐year‐old diabetic male was on treatment for diabetic nonhealing ulcer involving right foot and sole for the past 6 months. Linezolid was started based on the culture and sensitivity of the pus. Patient developed thrombocytopenia and black hairy tongue after 7 days of the drug regimen. Drug was stopped and patient was advised to maintain good oral hygiene, soft tooth brush for brushing and regular mouth wash with lukewarm water. The black hairy tongue completely resolved within a week after stopping the drug. The taste and foreign body sensation on the tongue while swallowing were also improved. The diabetic wound was treated by starting vancomycin after giving a surgical wound debridement by a general surgeon.